Application of Knowledge and Skills Competency of Elementary School Students in Science Subject in Vietnam - Nguyen, Hieu Huu; Duong, Huong Giang Thien (Jurnal Penelitian dan Pembelajaran IPA, 2025)
In Vietnam's 2018 General Education Program for Science, the applied knowledge and skills competency is one of the three components of natural scientific competency (Ministry of Education and Training, 2018a). The applied knowledge and skills competency refers to learners' ability to comprehensively mobilize acquired knowledge and skills and apply them to effectively identify and solve real-world problems in specific contexts. The implementation of the Science subject in elementary schools currently reveals that, although the curriculum includes descriptions of indicators for this competency, and teachers have employed several measures to develop it, the absence of a competency framework with specific competency components and behavioral indicators makes it challenging for teachers to select teaching strategies and effectively assess students' competency development. This study employs the PRISMA systematic review method and benchmarking method to identify the overlapping indicators of the applied knowledge and skills competency in Science subject of the Vietnam’s General Education Program and the scientific competency frameworks of PISA and several other countries. Based on this analysis, a competency framework for applying knowledge and skills in Science appropriate for Vietnamese elementary students was proposed. The proposed framework was refined through expert consultation using the Delphi method and consists of five components and twelve competency indicators.